Walled structures and settlement patterns in the south-western part of Dhofar, Oman (poster) - Garba , Roman; Farrington, Peter (Proceedings of the Seminar for Arabian Studies, 2011)
This poster summarizes the mapping of walled structures found in two sites of the Dhofar (Żufar) region of Oman. Satellite imagery research and field investigations of the first area revealed a vast site enclosed by wall structures, measuring 913 × 398 m at its longest and widest points respectively. Many stone structures, including graves, were found in the vicinity. Collected documentation suggests it may be part of a major pre-Islamic settlement associated with the frankincense and spice trade. The second site is smaller, but its walls also contained similar tower-like structures. The research area lies in the south-western part of Dhofar near the Oman-Yemen border.